Game of Eyeballs: What Should Be Above and Below the Fold of an E-Commerce Website: A Biometric Study - Shahrukh Nadeem; Humza Mahfooz (International Journal of Experiential Learning & Case Studies, 2019)
With the advent of Web 2.0, there has been a comprehensive paradigm shift in the way people communicate and interact on the web. While the time before the Y2K focused on unilateral communication from the website owners to the viewers; the modern era has brought with it a whole new dimension of how organizations interact with their customers and prospects online. One of the major components of this ecosystem is the buzzing industry of E-Commerce. Today, amongst the top five most swiftly growing industries globally commerce is one of them. Organizations have made a beeline to market their products online to get their fair share of the online tech-savvy customers. In Pakistan, the E-Commerce marketplace is set to cross the magical USD1Billion this year. It is a big feat in a country where online payments are still not applicable and most of the business is done on Cash on Delivery. The purpose of this research is to narrow down on the subliminal and overt factors which contribute to making an E-Commerce platform/website stand out. The study takes into account the neurological factors that include eye-tracking as well as emotional recognition tools to study how online consumers interact with a particular website. The results revealed very interesting facts about how users interact with a particular E-Commerce website where findings revealed that most of the attention is given to data above the fold while screen flashers are the most premium real estate for these websites. Additionally, the space below the fold should not be ignored by these websites since most of the shoppers scroll down unconsciously. In order to promote engagement, these websites should focus on promoting discounts and sales messages.